Adult Umbilical Reconstruction : Principles and Techniques - Shiffman, Melvin A. (Springer International Publishing : Imprint: Springer, 2017)
This book starts with a description of the anatomy of the umbilicus and its ideal shape. After a brief summary of the history of umbilical reconstruction, currently used umbilical reconstructive techniques are presented. The reader will also find information on the reconstruction of the umbilicus after malignant melanoma; outcomes and complications will be discussed in the last chapters. Written by respected authors, this book will offer residents and fellows as well as practicing and highly experienced plastic surgeons essential guidance on treatment and decision-making concerning umbilical reconstruction. Its numerous illustrations and clearly structured content make the book a must-read.
Keywords: Medicine.; Plastic surgery.; elektronické knihy; electronic books